Frankia-actinorhizal symbiosis: a non-chemical biological assemblage for enhanced plant growth, nodulation and reclamation of degraded soils - Bhattacharyya, Pranaba Nanda; Islam, Nazim Forid; Sarma, Bhaskar; Nath, Bharat Chandra; Al-Ani, Laith Khalil Tawfeeq; Lesueur, Didier (Springer, 2024)
Actinorhizal symbiosis naturally harbours beneficial categories of diverse plant growth promoting microorganisms (PGPMs), including the Frankia species. The beneficial microorganisms can be used as efficient, non-chemical and sustainable alternatives for adopting effective soil restoration programmes and revegetation schedules in chemical and industrial-contaminated sites, including treating degraded lands contaminated with toxic chemicals and pesticides. It has been proposed that the interactions between the microbial gene pool are of immense agricultural significance that would facilitate an improvement in the health, hygiene and nutrient acquisition pathway of native soil. The present review is focused on exploiting the hithertounexplored Frankia-actinorhizal symbiosis with due interest for their application in soil restoration programmes, including the reclamation of degraded lands. This opens up new insights for the development of sustainability in forestry and plantation research. Additionally, it would promise an improvement in plant growth and vigour, hygiene, and other parameters related to crop yield, such as plant biomass, root/shoot ratio, crop yield, and so on. Novel and putative microorganisms isolated from the actinorhizal may be used for bio-transformation of allelochemicals and toxic heavy metals into compounds with modified biological properties, opening up novel avenues for mediating microbial degradation of putative allelochemicals that would otherwise accumulate at phytotoxic levels in soil. Endophyte-host specificities, the phylogeny of Frankia, and the conservation of unique endemic plant genetic resources like actinorhizal plants, are of paramount significance in the advancement of genomics, metabolomics and phenomics.